2021
DOI: 10.1016/j.jbc.2021.101434
|View full text |Cite
|
Sign up to set email alerts
|

Malonyl-acyl carrier protein decarboxylase activity promotes fatty acid and cell envelope biosynthesis in Proteobacteria

Abstract: Bacterial fatty acid synthesis in Escherichia coli is initiated by the condensation of an acetyl-CoA with a malonyl-acyl carrier protein (ACP) by the β-ketoacyl-ACP synthase III enzyme, FabH. E. coli Δ fabH knockout strains are viable because of the yiiD gene that allows FabH-independent fatty acid synthesis initiation. However, the molecular function of the yiiD gene product is not known. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…Again, some of these genes (such as walK and vraG in cohort B) are known to be associated with vancomycin resistance but were not identified in the mutations analysis, highlighting the potential of the gene-burden test to increase the power of GWAS. A strong association was found with the SAUSA300_0956 locus, a GNAT-family acetyltransferase (Majorek, Osinski et al 2017, Whaley, Radka et al 2021). The function of the protein in S. aureus is not well understood, however, some indirect evidence may point to a role in cell-wall synthesis or turn-over.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Again, some of these genes (such as walK and vraG in cohort B) are known to be associated with vancomycin resistance but were not identified in the mutations analysis, highlighting the potential of the gene-burden test to increase the power of GWAS. A strong association was found with the SAUSA300_0956 locus, a GNAT-family acetyltransferase (Majorek, Osinski et al 2017, Whaley, Radka et al 2021). The function of the protein in S. aureus is not well understood, however, some indirect evidence may point to a role in cell-wall synthesis or turn-over.…”
Section: Resultsmentioning
confidence: 99%
“…First, it is located between the autolysin atl and the methicillin resistance factor fmtA (Qamar and Golemi-Kotra 2012) . Second, an E. coli homolog of SAUSA300_0956 was linked to membrane biosynthesis (Whaley, Radka et al 2021). Another interest association involved the SAUSA300_1220 locus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this essentiality is bypassed by the product of the yiiD gene (renamed MadA) (49). The bypass mechanism involves the decarboxylation of malonyl ACP to produce acetyl ACP (50). Unlike acetyl CoA, which can only be integrated into the initiation step of FA biosynthesis by FabH, this substrate can be used by FabB/FabF to bypass the loss of KAS III activity in E. coli (50).…”
Section: Discussionmentioning
confidence: 99%
“…The bypass mechanism involves the decarboxylation of malonyl ACP to produce acetyl ACP (50). Unlike acetyl CoA, which can only be integrated into the initiation step of FA biosynthesis by FabH, this substrate can be used by FabB/FabF to bypass the loss of KAS III activity in E. coli (50). However, the supply of FA to integrate into membrane biogenesis by the MadA bypass is highly restrictive, and as such, earlier E. coli K-12 studies reported that Δ fabH cells are tiny (26, 27).…”
Section: Discussionmentioning
confidence: 99%